DIGITAL MARKETING STRATEGY ANALYSIS OF PRODUCT PURCHASING DECISIONS AT THE TIKTOK SHOP - Kespandiar, Tengku; Mokhamad Arwani,; Saida Zainurossalamia ZA,; Silvia Ekasari,; Donny Dharmawan, (Journal of Innovation Research and Knowledge, 2024)
The aim of this research is to analyze digital marketing strategy analysis of product purchasing decisions at the TikTok Shop. This type of research is survey research. The population in this research are buyers who have a TikTok account and have shopped at the TikTok Shop. Because the population is so large, the sample taken was limited to 50 respondents. Data analysis in research uses simple linear regression using the partial (t) test. The research results show that electronic word of mouth has a positive and significant effect on product purchasing decisions at the TikTok Shop.